Novel Insights into the Nobilamide Family from a Deep-Sea Bacillus: Chemical Diversity, Biosynthesis and Antimicrobial Activity Towards Multidrug-Resistant Bacteria - Vincenza Casella; Gerardo Della Sala; Silvia Scarpato; Carmine Buonocore; Costanza Ragozzino; Pietro Tedesco; Daniela Coppola; Giovanni Andrea Vitale; Donatella de Pascale; Fortunato Palma Esposito (Marine Drugs)
With rising concerns about antimicrobial resistance, the identification of new lead compounds to target multidrug-resistant bacteria is essential. This study employed a fast miniaturized screening to simultaneously cultivate and evaluate about 300 marine strains for biosurfactant and antibacterial activities, leading to the selection of the deep-sea Bacillus halotolerans BCP32. The integration of tandem mass spectrometry molecular networking and bioassay-guided fractionation unveiled this strain as a prolific factory of surfactins and nobilamides. Particularly, 84 nobilamide congeners were identified in the bacterial exometabolome, 71 of them being novel metabolites. Among these, four major compounds were isolated, including the known TL-119 and nobilamide I, as well as the two new nobilamides T1 and S1. TL-119 and nobilamide S1 exhibited potent antibiotic activity against various multidrug-resistant Staphylococcus strains and other Gram-positive pathogens, including the foodborne pathogen Listeria monocytogenes. Finally, in silico analysis of Bacillus halotolerans BCP32 genome revealed nobilamide biosynthesis to be directed by a previously unknown heptamodular nonribosomal peptide synthetase.